You are here - Smith, Jennifer E. 1980- (Simon & Schuster Books for Young Readers, 2009)
Sixteen-year-old Emma Healy has never felt that she fit in with the rest of her family, so when she discovers that she had a twin brother who died shortly after they were born, she takes off on an impulsive road trip to try to discover who she really is. -- Ages 13 up.
Keywords: Automobile travel -- Fiction; Identity -- Fiction; Individuality -- Fiction; Death -- Fiction; Twins -- Fiction; Families -- Fiction; Dogs -- Fiction; Jugendbuch